EVOLUTIONARY RESPONSES OF A COCCOLITHOPHORID GEPHYROCAPSA OCEANICA TO OCEAN ACIDIFICATION - Jin, Peng; Gao, Kunshan; Beardall, John; 高坤山 (WILEY-BLACKWELL, 2013)
National Basic Research Program of China [2009CB421207]; National Natural Science Foundation [40930846, 41120164007]; China-Japan collaboration project from MOST [S2012GR0290]; "111" project from Ministry of Education The ongoing ocean acidification associated with a changing carbonate system may impose profound effects on marine planktonic calcifiers. Here, we show that a coccolithophore, Gephyrocapsa oceanica, evolved in response to an elevated CO2 concentration of 1000 atm (pH reduced to 7.8) in a long-term (approximate to 670 generations) selection experiment. The high CO2-selected cells showed increases in photosynthetic carbon fixation, growth rate, cellular particulate organic carbon (POC) or nitrogen (PON) production, and a decrease in C:N elemental ratio, indicating a greater upregulation of PON than of POC production under the ocean acidification condition. Cells from the low CO2 selection process shifted to high CO2 exposure showed an enhanced cellular POC and PON production rates. Our data suggest that the coccolithophorid could adapt to ocean acidification with enhanced assimilations of carbon and nitrogen but decreased C:N ratios.